2011
DOI: 10.4021/jem23w
|View full text |Cite
|
Sign up to set email alerts
|

Role of Vitamin D in Diabetes

Abstract: The role of vitamin D in the pathogenesis and prevention of diabetes has sparked widespread interest. Vitamin D receptors are present in both pancreatic beta-cells and immune cells. Beside its classical role as the major regulator for calcium absorption, vitamin D mediates the activity of beta-cell calcium-dependent endopeptidases promotes conversion of proinsulin to insulin and increases insulin output. In peripheral insulin target tissues, vitamin D enhances insulin action via regulation of the calcium pool.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 33 publications
0
34
0
2
Order By: Relevance
“…This inflammatory condition will affect the pancreatic beta cells and reduce its function. [16] In a study by Hussain MJ et al, [17] TNF-α and soluble IL-2 receptor were found to be increased in patients with T1 DM, and also in their first generation. In this study, two T1 DM patients had normal vitamin D level, while the level of C-Peptide was low and the level of IL-2 was high.…”
Section: Discussionmentioning
confidence: 97%
“…This inflammatory condition will affect the pancreatic beta cells and reduce its function. [16] In a study by Hussain MJ et al, [17] TNF-α and soluble IL-2 receptor were found to be increased in patients with T1 DM, and also in their first generation. In this study, two T1 DM patients had normal vitamin D level, while the level of C-Peptide was low and the level of IL-2 was high.…”
Section: Discussionmentioning
confidence: 97%
“…25 Micronutrient deficiencies among diabetic patients have also been postulated to increase the risk of DM and TB. Notably, vitamin D deficiency has been demonstrated to increase both the risk of DM 26 and TB. 27 Vitamin D is directly essential in inducing pancreatic A cell secretion of insulin by increasing intracellular influx of calcium.…”
Section: Mechanisms Of Association Between Tb and Dmmentioning
confidence: 98%
“…The skeletal action of Vitamin D is to maintain calcium homeostasis and bone health. In addition, it is now known to be involved in extra-skeletal functions in diverse tissues and organs, including the pancreas, heart, brain and immunomodulation [6]- [8]. Several clinical studies suggest the possible association between low Vitamin D levels and potential adverse outcomes of pregnancy [9]- [12].…”
Section: Introductionmentioning
confidence: 99%